Estudo osteológico e miológico do crânio de Opisthocomus hoazin (Müller, 1776) (Aves: Opisthocomidae), comparado com algumas espécies de Cracidae, Musophagidae e Cuculidae - Marceliano, Maria Luiza Videira (Museu Paraense Emilio Goeldi, 2016)
Opisthocomus hoazm (Müller, 1776) an endemic species of the amazon region and sole representative of the Opisthocomidae fami/y, is still a matter ofdispute in terms of its position in systematics. Thís study analyzed the bone and muscle skull structures of O. hoazm and compared them to those of 15 of species the Cracidae (Ortalis motmot, Penelope pileata, Pipile cujubi, Nothocrax urumutum, Mitu tuberosa and Crax alector), Musophagidae (Musophaga violacea, Tauraco erythrolophus, Tauraco harthlaubi and Tauraco leucotis) and Cuculidae families (Coccyzus americanus, Coccyzus melacorynchus, Piayacayana, Crotophaga ani and Guira guira). The banes and muscles of the O. hoazm species were described in detail and used as a reference in order to compare the many anatomic strutures with those ofthe above mentioned species. This study of the anatomy of the skull showed that O. hoazm has specific features. although ir seems to be more related to Musophagidae in some aspects, and to Cuculidae in orthers. O. hoazm has Uttte affinity with Cracidae, however. It És still difficult to relate O. hoazm with any of any ofthese taxons, based on bone and muscle skl.l11features. It is conveniente at lhe present time to maintain it in the monotypical Opisthocomiformes Order.